FORMATION OF SPEECH COMMUNICATION CULTURE OF PRIMARY SCHOOL STUDENTS USING THE NEWEST TECHNOLOGIES - Verbeschuk, Svetlana; Bai, Ihor; Vysochan, Lesia (Mountain School of Ukrainian Carpaty, 2023)
The article examines the formation of the culture of speech communication of primary school students, reveals the latest technologies that are recommended for use by the New Ukrainian School. In the article outlines the characteristic features of culture speech communication junior pupils by means of new technologies. Analyzes the basic concept of «speech culture» and «culture of speech». Proved, that culture is a specific characteristic of society and determines the level of historical development. Accumulated today in Ukraine and abroad experience convincingly demonstrates that interactive methods promote intensification and optimization of the educational process. Disclosed basic concepts the level of speech culture of the personality.